Crystal structure of bis{N′-[1,3-diphenylprop-2-en-1-ylidene]-N-phenylcarbamohydrazonothioato}zinc(II), C44H36N6S2Zn - Tan, Ming Yueh; Crouse, Karen A.; Tan, Sang Loon *; Tiekink, Edward R. T. * (De Gruyter Open, 2023)
C44H36N6S2Zn, monoclinic, P21/c (no. 14), a = 14.5676(4) Å, b = 26.1767(8) Å, c = 10.0963(3) Å, β = 99.140(3)°, V = 3801.2(2) Å3, Z = 4, Rgt(F) = 0.0397, wRref(F2) = 0.1000, T = 100 K.